The Wordsworth Word Finder - McCutcheon, Marc (Wordsworth Editions Ltd, 1997)
This is an ingenious combination of a reverse dictionary, a thesaurus and a visual dictionary without pictures.
Keywords: English Language; Reference; General; Reference; Thesauri; Thesauri